KENAKALAN ANAK (JUVENILE DELINQUENCY) DITINJAU DARI KRIMINOLOGI (PERSPEKTIF TEORI ANOMIE) - Ruslan, Muhammad Ibnu Maulana; Maulana, Muhammad (Muhammadiyah Makassar University, 2024)
AbstrackThis research examines juvenile delinquency from the perspective of anomie theory. Juvenile delinquency is a social phenomenon of serious concern in modern society. It encompasses various deviant behaviors committed by individuals who have not reached adulthood. This phenomenon has significant impacts not only on the individuals involved but also on society as a whole.The study employs a normative juridical method by examining literature or secondary data as the basis for research, conducting searches on regulations and literature related to the issues under investigation.The results indicate that the emergence of juvenile delinquency from the perspective of anomie theory can occur because a child responds to the discrepancy between what they expect in a high social life and the limitations of the resources they have. Other contributing factors may also originate from internal and external factors. Some of these factors include: a. Lack of education for children, b. Lack of parental role, c. Instability in social, political, and economic conditions, and d. Moral decline in children.Keywords: Juvenile delinquency, Criminology, Anomie Theory